Cefaleia cervicogénica. - C Correia; P Monteiro (Acta Médica Portuguesa, 1992)
It has been known for many years that headaches can originate from abnormalities in the neck. However, their clinical pictures were never sufficiently systematized, at least not enough to allows for research on their pathogenesis. In 1983 Sjaastad et al. described a group of patients with a very uniform and stereotyped headache. Attacks of mild, longlasting, unilateral head pain without side-shift, occurred every few weeks. The headache could be provoked by neck movements, such as extension, rotation or lateral flexion, as well as by external pressure on the neck, eventually spreading to the ipsilateral orbito-frontal-temporal or facial areas. The denomination Cervicogenic Headache (CC) was proposed. Its pathophysiology is presently unknown. The C2 and occipital nerve blockages eliminate the pain. The authors present a typical CC case and make some comments on its clinical picture, pathophysiology, and treatment.